Is flood water safe for consumption at evacuation centre in kuala krai district, kelantan, malaysia?. Issue 1 (March 2021) - Nayan, N; Hashim, M; Saleh, Y; Mahat, H; See, K L; Khotimah, N; Setyowati, D L
Abstract: Clean water supply has an important role among flood victims at evacuation centers during the flood. However, the water supply from various unknown and unverified sources such as hygiene status can affect the flood victims health. Therefore, the purpose of this study is to evaluate the flood water quality in the Kuala Krai flooding areas. The methodology of data collection in this study are fieldwork methods. It has been used to collect flood water samples during the northeast monsoon season in December 2016 and January 2017. A total of four flood water stations have been select based on the four flood evacuation centers based on the number of flood victims. A total of 13 water quality parameters were analyzed: pH, DO, BOD, COD, SS, NH3N, turbidity, NO3, Fe, Mg, Ca, Cu and E. coli bacteria. Flood water quality assessment in this study is based on the Malaysian National Water Quality Standards by the Malaysia Department of Environment (DOE). The results showed that flood water quality was in class III which was considered as moderate pollution. This situation explains that flood water needs to be fully treated for drinking water. To ensure the safe water supply for flood victims, a water supply risk management during floods has to be developed to ensure flood victims will have a good clean water supply and reduce the spread of flood-related diseases.